Born between war and peace: Situating peacekeeper-fathered children in research on children born of war - Wagner, Kirstin; Tasker, Heather; Vahedi, Luissa; Bartels, Susan A.; Lee, Sabine (Frontiers in Political Science, 2022)
In the last two decades, academic research has made significant progress exploring the life courses of so-called “children born of war” (CBOW). Similarly, the unintended consequences of peacekeeping operations, including the experiences of victims of sexual exploitation and abuse, and children born of these interactions, have received preliminary academic attention. This paper compares peacekeeper-fathered children (PKFC) to other CBOW to determine how these two groups relate to one another. We draw on research conducted in two peacekeeping contexts where personnel have been accused of fathering and abandoning children (Haiti and the Democratic Republic of Congo) to empirically situate PKFC within the category of CBOW. We introduce 5,388 micro-narratives from Haitian and Congolese community members (Haiti n = 2,541, DRC = 2,858) and 113 qualitative interviews with mothers/grandmothers of PKFC (Haiti n = 18, DRC n = 60) and PKFC (DRC n = 35) to investigate how PKFC fit in the CBOW paradigm. Our findings demonstrate that many of the multi-level adversities faced by PKFC resemble those of the broader reference group. Given their shared developmental needs and experiences of exclusion, we conclude that PKFC constitute CBOW and ought to be included in conceptualisations pertaining to them. Acknowledging PKFC as CBOW offers new opportunities for policy development to (a) enhance protection and support of all CBOW and (b) remind states of their commitments to uphold the rights of all children.